The quest of Zainul Abedin - Jahangir, Burhanuddin Khan.; International Centre for Bengali Studies (Dhaka, Bangladesh : International Centre for Bengal Studies : Distributor, University Press, 1993)
Social problems in the art of Zainul Abedin, Bangladeshi painter.
Includes bibliographical references.
Keywords: Abedin, Zainul, -- 1914-1976 -- Criticism and interpretation; Social problems in art